Pengaruh Kompetensi dan Kompensasi Finansial terhadap Kinerja Karyawan dengan Komitmen Organisasi sebagai Variabel Moderasi pada PT. Astra Motor Cabang Mataram - Maniza, Lalu Hendra; Sudarta; Vinuzia, Mala (Valid: Jurnal Ilmiah, 2025)
This study is motivated by the importance of improving employee performance as a determining factor for organizational success, particularly through competency management, financial compensation, and organizational commitment. The purpose of this study is to analyze the partial and simultaneous effects of competency and financial compensation on employee performance and to examine the role of organizational commitment as a moderating variable at PT. Astra Motor Mataram Branch. This study uses a quantitative approach with a sample of 50 employees. Data collection techniques were carried out through questionnaires and documentation. Data analysis used multiple linear regression and Moderated Regression Analysis (MRA). The results showed that competency and financial compensation had a significant partial and simultaneous effect on employee performance. Furthermore, organizational commitment was found to moderate the influence of competency and financial compensation on employee performance. This study recommends that company leaders improve competency development, fair compensation systems, and strengthen organizational commitment to achieve optimal and sustainable employee performance.